First record of the genus Loxopsis from the Philippines with the discovery of two new species (Phasmida, Diapheromeridae, Necrosciinae) - Bresseel, Joachim (Zootaxa, 2012)
The genus Loxopsis Westwood, 1859 is reported from the Philippines for the first time. Two new species on the island of Mind-anao are described and figured from both sexes: Loxopsis sarmientoi n. sp. from Mt. Parker and Loxopsis tboli n. sp. from LakeSebu. The specimen identified as Loxopsis tuberculata Redtenbacher, 1908 by Klante (1975) represents a different, unde-scribed species which belongs in Paraloxopsis Günther, 1932. The concerned specimen is briefly described and illustrated. A key to the species of Loxopsis Westwood, 1859 is presented